Cardiac expression of HMOX1 and PGF in sickle cell mice and haem‐treated wild type mice dominates organ expression profiles via Nrf2 (Nfe2l2). (6th August 2019) - Gbotosho, Oluwabukola T.; Ghosh, Samit; Kapetanaki, Maria G.; Lin, Yu; Weidert, Frances; Bullock, Grant C.; Ofori‐Acquah, Solomon F.; Kato, Gregory J.
Summary: Haemolysis is a major feature of sickle cell disease (SCD) that contributes to organ damage. It is well established that haem, a product of haemolysis, induces expression of the enzyme that degrades it, haem oxygenase‐1 (HMOX1). We have also shown that haem induces expression of placental growth factor (PGF), but the organ specificity of these responses has not been well‐defined. As expected, we found high level expression of Hmox1 and Pgf transcripts in the reticuloendothelial system organs of transgenic sickle cell mice, but surprisingly strong expression in the heart ( P < 0·0001). This pattern was largely replicated in wild type mice by intravenous injection of exogenous haem. In the heart, haem induced unexpectedly strong mRNA responses for Hmox1 (18‐fold), Pgf (4‐fold), and the haem transporter Slc48a1 (also termed Hrg1 ; 2·4‐fold). This was comparable to the liver, the principal known haem‐detoxifying organ. The NFE2L2 (also termed NRF2 ) transcription factor mediated much of the haem induction of Hmox1 and Hrg1 in all organs, but less so for Pgf . Our results indicate that the heart expresses haem response pathway genes at surprisingly high basal levels and shares with the liver a similar transcriptional response to circulating haem. The role of the heart in haem response should be investigated further.